2020
DOI: 10.1021/acs.jafc.0c00703
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrase Complexes Rich in Xylanases and Arabinofuranosidases Affect the Autofluorescence Signal and Liberate Phenolic Acids from the Cell Wall Matrix in Wheat, Maize, and Rice Bran: An In Vitro Digestion Study

Abstract: The high fiber content of cereal coproducts used in animal feed reduces the digestibility and nutrient availability. Therefore, the aim of this study was to elucidate the ability of two carbohydrase complexes to degrade the cell wall of wheat, maize, and rice during in vitro digestion. One complex was rich in cell-wall-degrading enzymes (NSPase 1), and the other was similar but additionally enriched with xylanases and arabinofuranosidases (NSPase 2). Degradation of arabinoxylan, the main cereal cell wall polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Phenolic acids are known for their antioxidative and antimicrobial properties and have also been shown to reduce methane production [ 8 ]. These compounds are also found in high concentrations in cereals such as wheat and maize, with ferulic acid being the main phenolic acid component in the cross-linking of arabinoxylan, the main cereal cell wall polysaccharide [ 28 ]. However, phenolic acids in cereals are known to be present mainly as glycoside or glucuronide conjugates [ 28 , 29 ], and our results indicate that the opposite is observed in seaweeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic acids are known for their antioxidative and antimicrobial properties and have also been shown to reduce methane production [ 8 ]. These compounds are also found in high concentrations in cereals such as wheat and maize, with ferulic acid being the main phenolic acid component in the cross-linking of arabinoxylan, the main cereal cell wall polysaccharide [ 28 ]. However, phenolic acids in cereals are known to be present mainly as glycoside or glucuronide conjugates [ 28 , 29 ], and our results indicate that the opposite is observed in seaweeds.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are also found in high concentrations in cereals such as wheat and maize, with ferulic acid being the main phenolic acid component in the cross-linking of arabinoxylan, the main cereal cell wall polysaccharide [ 28 ]. However, phenolic acids in cereals are known to be present mainly as glycoside or glucuronide conjugates [ 28 , 29 ], and our results indicate that the opposite is observed in seaweeds. Furthermore, sulfate itself and sulfur-containing compounds, known as organosulfur compounds, have also been shown to reduce methane production [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crosslinked arabinoxylan, via DFA and TriFA bridges, further reduces the degradation and fermentability of fiber in DDGScontaining diets. 5,18,29 The observation that the disappearance of bound coumaric acid in corn-based diets is less than 50% indicates that bound coumaric acid is resistant to enzymatic hydrolysis, and thus, contributes to reduced degradation of arabinoxylans in corn fiber. The observed low disappearance (i.e., ∼35%) of bound ferulic acid in diets containing corn and DDGS indicates that pigs have low capacity to digest and ferment bound ferulic acid from the arabinoxylan complex in corn or DDGS.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that concentrations of bound phenolic acids in feces from pigs fed the corn‐SBM‐DDGS diet were greater than in feces from pigs fed the corn‐SBM diet demonstrates that bound phenolic acids in DDGS‐containing diets are poorly fermented by pigs. Crosslinked arabinoxylan, via DFA and TriFA bridges, further reduces the degradation and fermentability of fiber in DDGS‐containing diets 5,18,29 …”
Section: Discussionmentioning
confidence: 99%
“…However, NSPs are also an important nutrient for monogastric animals, especially for gut bacteria fermentation, which depends on the NSP components. It has been reported that exogenous addition of non-starch polysaccharide degrading enzymes (especially xylanase, XYL) can degrade insoluble and large soluble polysaccharides in the diet to produce oligosaccharides [ 9 , 10 ], oligosaccharides can be well fermented by intestinal bacteria. In addition, xylo-oligosaccarides (XOS) with a degree of polymerization in the range of 2–6, were identified to improve intestinal health and stimulate immune responses in animals, acting in a prebiotic manner [ 11 ].…”
Section: Introductionmentioning
confidence: 99%